THE IMPORTANCE OF THE TOURISM TRADE AND ITS STAGES OF DEVELOPMENT - Umirov Sherzod Baxriddinovich (Ecomind Press, 2025)
This scientific article analyzes the development stages of tourism trade. The author researched the development stages of tourism divided into five major periods.
Keywords: Tourism trade, international trade, social tourism, psychological tourism, tourism and local population, stagnation, stages of development.